Effects of BF2 and B implantation-doping on crystalline degradation of pseudomorphic metastable Ge0.06Si0.94 - Im, S; Oh, MS; Joo, MH; Kim, HB; Kim, HK; Song, JH (JAPAN SOC APPLIED PHYSICS, 1998)
Pseudomorphic metastable Ge0.06Si0.94 layers grown by molecular beam epitaxy (MBE) on Si (100) substrates were implanted at room temperature by 70 keV BF2 ions with two different doses of 3 x 10(13) and 2.5 x 10(14) cm(-2), or by 16 keV B ions with a dose of 4 x 10(14) cm(-2). The implanted samples were subsequently annealed at 800 and 900 degrees C for 30 min in a vacuum tube furnace. Observed by 2 MeV He-4 channeling spectrometry before annealing, only the sample implanted at a dose of 2.5 x 10(14) BS cm(-2) is amorphized from surface to a depth of about 90 nm. Crystalline degradation of post-annealed Ge0.06Si0.94 samples becomes pronounced as the dose increases. Even though the both samples implanted with 3 x 10(13) BF2 cm(-2) and 4 x 10(14) B cm(-2) initially show almost the same levels of radiation damage in the channeling spectra, the sample implanted at 3 x 10(13) BF2 cm(-2) only conserves the same crystalline quality as the as-grown GeSi after being annealed. It is concluded that such a low dose of 3 x 10(13) BF2 cm(-2) can be doped by implantation without causing radiation or strain-induced defects in the pseudomorphic GeSi.
Keywords: HETEROJUNCTION BIPOLAR-TRANSISTORS